Fondasi Psikologi Pendidikan Anak Usia Dini Berbasis Hadis: Studi Literatur Sistematis - Andini, Arfah; Marhumah, Marhumah; Khoiriyatul Muyassaroh, Iffah (El Nubuwwah Jurnal Studi Hadis, 2025)
Studies on early childhood education psychology from the perspective of Prophetic hadith have largely relied on normative and fragmented approaches, resulting in limited understanding of hadith as an applied pedagogical framework. This study aims to systematically examine how the hadith of Prophet Muhammad (peace be upon him) are interpreted and utilized in Indonesian academic literature as foundational principles for early childhood education psychology. This research employs a Systematic Literature Review (SLR) method by analyzing 33 scholarly articles published between 2019 and 2024 that are relevant to early childhood education and hadith studies. The analysis follows stages of identification, relevance classification, and thematic synthesis based on research focus and methodological approaches. The findings indicate that hadith are positioned not merely as sources of moral and spiritual values but also as pedagogical guidelines encompassing concepts of fitrah, compassion, exemplary conduct, habituation, and parental responsibility as primary educators. The review also reveals significant challenges in implementing hadith-based educational principles, particularly related to limited pedagogical competence among early childhood educators, lack of contextual teaching materials, and insufficient parental literacy in hadith studies. This study concludes that strengthening the integration of hadith and early childhood education psychology requires a more contextual and collaborative approach involving families, educational institutions, and policymakers to promote holistic, character-based early childhood education grounded in revealed values.